Pattern, predictors and recurrence of cervical lymph node metastases in papillary thyroid cancer - Shi, Lan; Song, Haiping; Zhu, Huiping; Li, Dapeng; Zhang, Ning (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: This study investigated the pattern, predictors, and recurrence of node metastasis in papillary thyroid cancer patients. Material and methods: One hundred and 65 papillary thyroid cancer (PTC) patients who underwent total thyroidectomy and cervical lymph node (LN) dissection (LND), in which more than 12 lymph nodes were dissected, were examined. The nodes were classified from levels I to VI. Final pathologic diagnosis of positive lymph node metastases in the differential node levels was determined. Results: Cervical metastases of PTC were most commonly encountered in level VI, followed by levels III and IV, and then levels II and V. Metastases in level I seldom occurred. Skip metastases occurred in nine patients. Univariate analysis suggested that multifocality and extracapsular invasion were associated with LN metastases. The metastatic ratio for micro PTC and local canceration derived from benign lesions and encapsulation was low. Multivariate analysis showed that LN metastases were closely related to invasion of the thyroid capsule and primary PTC. Standardized estimation showed that the encapsulating pattern had the greatest impact on developing cervical LN metastases. Lymph node recurrence was observed in 11 patients. Conclusions : The metastatic pattern of PTC assists in delineating the extent of selective LND. Routine bilateral central node dissection at the time of thyroidectomy is recommended. Comprehensive selective LND is recommended in multifocal PTC and with capsular invasion.